Deep-sea squat lobsters of the genus Paramunida Baba, 1988 (Crustacea: Decapoda: Munididae) from north-western Australia: new records and description of three new species - Mccallum, Anna W.; Cabezas, Patricia; Andreakis, Nikos (Zootaxa, 2016)
Six species of Paramunida are reported from the continental margin of north-western Australia. Three species are new to science: Paramunida christinae sp. nov., P. ioannis sp. nov., and P. spiniantennata sp. nov. Two species are reported for the first time from Australian waters, P. evexa Macpherson, 1996 and P. tricarinata (Alcock, 1894). These species were confirmed by molecular evidence from the mitochondrial markers ND1 and 16S. We also examine phylogenetic relationships within the genus, and provide an identification key for all known Paramunida species.